THE BUILDER?S LIABILITY BEYOND THE DEFECTS LIABILITY - Johnson I IKPO (Institute of Research and Community Outreach - Petra Christian University, 2005)
This paper reviews the obligations of a builder after the expiration of the contracted defects liability period using relevant decided cases. The common areas identified as forming the bedrock of litigation pertain to structural and dimensional stability, freedom from damp, durability, adequate drainage, good waste disposal works, and effective service installations. Particular reference is made to walls, roofs, and services, which from the pilot study account for about 46%, 23%, and 17% respectively of the total defects attributable to the builder. It is concluded that the builder is responsible for defects arising from his product till the effluxion of reasonable time, except he establishes an element of contributory negligence.